Role of intercultural mediation in problem solving in a transatlantic network - Ribeiro, Sandra (2021)
Proceedings of AELFE-TAPP 2021 (19th AELFE Conference, 2nd TAPP Conference). Vilanova i la Geltrú (Barcelona), 7-9 July 2021